The Influence of Environmental Conditions on Pacing in Age Group Marathoners Competing in the “New York City Marathon” - Weiss, Katja; Valero, David; Villiger, Elias; Scheer, Volker; Thuany, Mabliny; Cuk, Ivan; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2022)
Background: The two aspects of the influence of environmental conditions on marathon running performance and pacing during a marathon have been separately and widely investigated. The influence of environmental conditions on the pacing of age group marathoners has, however, not been considered yet. Objective: The aim of the present study was to investigate the association between environmental conditions (i.e., temperature, barometric pressure, humidity, precipitation, sunshine, and cloud cover), gender and pacing of age group marathoners in the ‘New York City Marathon’. Methodology: Between 1999 and 2019, a total of 830,255 finishes (526,500 males and 303,755 females) were recorded. Time-adjusted averages of weather conditions for temperature, barometric pressure, humidity, and sunshine duration during the race were correlated with running speed in 5 km-intervals for age group runners in 10 year-intervals. Results: The running speed decreased with increasing temperatures in athletes of age groups 20-59 years with a pronounced negative effect for men aged 30 to 64 years and women aged 40 to 64 years. Higher levels of humidity were associated with faster running speeds for both sexes. Sunshine duration and barometric pressure showed no association with running speed. Conclusion: In summary, temperature and humidity affect pacing in age group marathoners differently. Specifically, increasing temperature slowed down runners of both sexes aged between 20 and 59 years, whereas increasing humidity slowed down runners of <20 and >80 years old.